Analysis of Football Players' Endurance Based on Playing Position: A Study of West Sumatra PON Players - Ridho Bahtra; John Arwandi (Gladi : Jurnal Ilmu Keolahragaan, 2026)
The problem of this study is the lack of empirical data on the endurance capabilities of West Sumatra PON soccer players based on playing positions based on sport science. Data on endurance capabilities is very important for coaches as a basis for developing measurable and structured training programs. The purpose of this study is to analyze the endurance capabilities of West Sumatra PON soccer players based on playing positions. This study uses a quantitative descriptive method with a survey approach. The sample in this study were 26 young soccer players. The instrument used was the yoyo intermittent recovery test. The collected data will be analyzed using statistical techniques with the help of SPSS 26 software and Microsoft Excel. From the test results, the mean value was 55.07, the standard deviation was 4.45, the minimum value was 47.49, and the maximum value was 63.22. Based on playing position, goalkeepers have an average VO2max of 51.69 (low), defenders 54.7 (moderate), full-backs 55.97 (moderate), midfielders 57.12 (moderate), wingers 56.36 (moderate), and forwards 52.64 (low). The results of this study generally indicate that players' endurance abilities are still not in accordance with the required endurance standards for soccer players. Coaches must improve players' endurance abilities in order to compete at the elite level. This data can be a reference for coaches to design and organize more effective training programs to improve players' endurance abilities.